The modern experience of the religious - Bravo, Nassim; Stewart, Jon 1961- (Leiden Boston Brill, 2023)
"The articles in The Modern Experience of the Religious, edited by Nassim Bravo and Jon Stewart, explore the many ways in which religion was impacted by the emergence of modernity, particularly after the Enlightenment, which underscored the centrality of human reason and thus called into question traditional forms of religiosity. Modernity raised several questions that are studied by the authors of this volume: What should be the role of religion in a secular or pluralistic society? How does the human being relate to God? Can instituted religion be compatible with modern values such as civil liberties, pluralism or environmentalism?"--
Literaturangaben
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion and sociology; Civilization, Modern; Aufsatzsammlung